Knowledge of Medicinal Plants for Children Diseases in the Environs of District Bannu, Khyber Pakhtoonkhwa (KPK) - Shaheen, Shabnam; Abbas, Safdar; Hussain, Javid; Mabood, Fazal; Umair, Muhammad; Ali, Maroof; Ahmad, Mushtaq; Zafar, Muhammad; Farooq, Umar; Khan, Ajmal (Frontiers in Pharmacology, 2017)
Medicinal plants are important treasures for the treatment of different types of diseases. Current study provides significant ethnopharmacological information, both qualitative and quantitative on medical plants related to children disorders from district Bannu, Khyber Pakhtunkhwa (KPK) province of Pakistan. The information gathered was quantitatively analyzed using informant consensus factor, relative frequency of citation and use value method to establish a baseline data for more comprehensive investigations of bioactive compounds of indigenous medicinal plants specifically related to children disorders. To best of our knowledge it is first attempt to document ethno-botanical information of medicinal plants using quantitative approaches. Total of 130 informants were interviewed using questionnaire conducted during 2014-2016 to identify the preparations and uses of the medicinal plants for children diseases treatment. A total of 55 species of flowering plants belonging to 49 genera and 32 families were used as ethno-medicines in the study area. The largest number of specie belong to Leguminosae and Cucurbitaceae families (4 species each) followed by Apiaceae, Moraceae, Poaceae, Rosaceae and Solanaceae (3 species each). In addition leaves and fruits are most used parts (28%), herbs are most used life form (47%), decoction method were used for administration (27%), and oral ingestion was the main used route of application (68.5%). The highest use value was reported for species Momordica charantia and Raphnus sativus (1 for each) and highest Informant Consensus Factor was observed for cardiovascular and rheumatic diseases categories (0.5 for each). Most of the species in the present study were used to cure gastrointestinal diseases (39 species). The results of present study revealed the importance of medicinal plant species and their significant role in the health care of the inhabitants in the present area. The people of Bannu own high traditional knowledge related to children diseases. In conclusion we recommend giving priority for further phytochemical investigation to plants that scored highest FIC, UV values, as such values could be considered as good indicator of prospective plants for discovering new drugs and attract future generations towards traditional healing practices.